Impact of Activator Ratio on Fly Ash-Based Geopolymer Concrete - Ramadhany, Ajmal; Herwani, Herwani; Faisal, Faisal (Fakultas Teknik Universitas Tanjungpura, 2025)
Geopolymer concrete is made by activating raw materials high in silica and alumina using alkaline activators. This material substitutes conventional Portland cement concrete by incorporating industrial waste materials like fly ash or metakaolin, which are recognized for reduced carbon emissions and superior chemical resistance. This study experimentally investigates the effect of the activator ratio (NaOH/Na₂SiO₃) on the alkali-silica reaction and the mechanical properties of geopolymer concrete made from fly ash, aiming to optimize the performance of this sustainable construction material. The experiment assesses various parameters, such as slump, volume weight, compressive strength, splitting tensile strength, and elastic modulus, using a constant 10M molar concentration for the activator solution with activator ratios of 1/2, 1/3, 1/4, and 1/5. The specimens used for the tests were cylindrical, measuring 10 cm x 20 cm for compressive strength tests and 15 cm x 30 cm for tests on split tensile strength and elastic modulus. Compressive strength was tested at 7, 14, and 28 days, while split tensile strength and elastic modulus were tested at 28 days. Results announced that increasing the Na₂SiO₃ concentration in the activator solution significantly affected the properties of geopolymer concrete. The optimal NaOH/Na₂SiO₃ ratio was found to be 1/5.